Critical readings in translation studies - Baker, Mona (Routledge, 2010)
Presents an overview of the developments in thinking about translation, both within and outside translation studies. This title covers the main forms of translation: oral, written, literary, non-literary, scientific, religious, audiovisual and machine translation. It also covers topics such as the politics and dynamics of representation